Full-band Monte Carlo simulation of single photon avalanche diodes - Dolgos, Denis; Meier, Hektor; Schenk, Andreas; Witzigmann, Bernd (2013 IEEE Photonics Conference, IPC 2013, 2013)
Single photon avalanche diodes (SPADs) enable a variety of innovative applications in the fields of biology, medicine, and physics. The propagation of single photons with optical fibers requires the usage of telecommunication wavelengths in the near infrared (NIR) spectral range. NIR SPADs, which can be employed for this application, consist of an absorber layer (In 0.53Ga0.47As) and a multiplication layer (InP or In 0.52Al0.48As). The product of the quantum efficiency ηq, the probability that the photoexcited carrier survives into the multiplier Pc, and the breakdown probability Pb that the carrier activates a self-sustaining avalanche designate the photon detection efficiency [1] PDE = ηqPcPb. The breakdown probability contributes primarily to the electric field dependence of the PDE and increases with the electric field. Therefore, a higher electric field enhances the photon detection efficiency. However, band-to-band or trap-assisted tunneling in the multiplication layer initiate dark counts and degrade the performance of SPAD devices at higher electric fields. Hence, to obtain a higher photon detection efficiency for a given increase of the electric field and tunneling rate, a steep rise of the breakdown probability with applied bias is favorable. The SPAD's timing jitter arises from various sources. The avalanche build-up time is the main contribution to the timing jitter [1]. © 2013 IEEE.
CRIS-Team Scopus Importer:2021-06-11